PATRIARKI DALAM PERSPEKTIF AGAMA ISLAM: Analisis Ayat-Ayat Al-Qur'an dan Hadis Berkaitan Dengan Gender dan Keadilan - Akmal, Muhammad (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
This research aims to examine the position of religious texts, particularly verses of the Qur'an and Hadith, in the construction and coloring of the patriarchal culture of Muslim society dominantly over time. The purpose of this research is to explore how the verses of the Qur'an and Hadith are interpreted to support or confront patriarchal norms. The type of research applied is qualitative research with secondary data, using literature study instruments from journals or articles that support relevant Quranic verses and a comparative approach to Hadith. From this study, it turns out that many classical interpretations of Quranic verses reinforce gender hierarchy, where the social position of women is often marginalized in all areas of social life. On the other hand, interpretations of Hadith show a more complex dynamic, where some Hadith support gender equality while others reinforce the patriarchal structure. This research makes an important contribution to understanding the relationship between religion and social structure, particularly in the context of gender justice. These findings not only open new avenues for discussion on the reinterpretation of religious texts but also offer critical perspectives that can support efforts to create gender equality in Muslim societies.